Author's View: a nuclear transcription factor relocalizing to mitochondria rescues cells from proteotoxic aggregates. (2nd January 2020) - Taskin, Asli Aras; Poveda-Huertes, Daniel; Vögtle, F.-Nora
ABSTRACT: Mitochondrial proteostasis is essential for survival, and imbalances can result in severe human diseases. We identified a novel stress response triggered upon accumulation of proteotoxic aggregates in the mitochondrial matrix. Mitochondria-to-nucleus signaling results in a transcriptional response and translocation of a nuclear transcription factor into mitochondria to maintain mitochondrial gene expression.